Polyphenols from blue honeysuckle (Lonicera caerulea var. edulis) berry inhibit lipid accumulation in adipocytes by suppressing lipogenesis. (28th October 2021) - Liu, Xinxin; Lv, Ying; Zheng, Mengyu; Yin, Li; Wang, Xiqing; Fu, Yujie; Yu, Bo; Li, Ji
Abstract: Ethnopharmacological relevance: Blue honeysuckle ( Lonicera caerulea var. edulis ) berry has been used in folk medicine for the treatment of bacterial infections, gastrointestinal disorders, and metabolic diseases. There is evidence to support its pharmacological effects in improving diabetes, fatty liver, and obesity. Aim of study: To investigate the effect of blue honeysuckle berry extract (BHBE) on lipid accumulation in adipocytes and the underlying mechanism. Materials and methods: High-performance liquid chromatography (HPLC) coupled with mass spectrometry (MS) was applied to analyze the polyphenolic compounds in BHBE. 3T3-L1 cells were used to induce into adipocytes. Oil Red O staining combined with triglyceride (TG) content determination were carried out to evaluate intracellular lipid accumulation. Western blot was used to determine the expression of lipogenic enzymes and transcription factors. Real-time PCR was used to determine the expression of lipolytic enzymes and adipocyte markers. Results: The primary polyphenols in BHBE are flavonoids (mainly flavonols and anthocyanins). BHBE dose-dependently inhibited lipid accumulation in adipocytes by reducing the expression of fatty acid synthase (FAS) and increasing the phosphorylation level of acetyl-CoA carboxylase (ACC). Moreover, BHBE was found to promote the phosphorylation of AMP-activated protein kinase (AMPK) and further reduce the expression of lipogenic transcription factors (PPARγ, C/EBPα, and SREBP-1c), while the selective AMPK inhibitor attenuated the suppressive effect of BHBE on lipogenesis. In addition, BHBE increased the expression of beige adipocyte markers ( Cd137 and Tmem26 ) and uncoupling protein 1 (UCP1) without affecting the expression of brown adipocyte markers ( Ebf3 and Eva1 ). Conclusion: BHBE inhibits lipid accumulation in adipocytes by suppressing lipogenesis via AMPK activation as well as by promoting beiging of adipocytes, which supports the anti-obesity potential of blue honeysuckle berry. Graphical abstract: Image 1 Highlights: Blue honeysuckle berry extract inhibited lipid accumulation in adipocytes. Blue honeysuckle berry extract suppressed lipogenesis via AMPK activation. Blue honeysuckle berry extract promoted beiging of adipocytes.